Safety assessment of Gram-negative bacteria associated with traditional French cheeses. (June 2019) - Imran, M.; Desmasures, N.; Coton, M.; Coton, E.; Le Flèche-Matéos, A.; Irlinger, F.; Delbès-Paus, C.; Stahl, V.; Montel, M.-C.; Vernoux, J.-P.
Abstract: Twenty Gram-negative bacterial (GNB) strains were selected based on the biodiversity previously observed in French traditional cheeses and their safety was assessed considering various safety criteria. For the majority of tested GNB strains, only gastric stress at pH 2 ( vs pH 4) resulted in low survival and no regrowth after an additional simulated gastro-intestinal stress. Presence of milk was shown to be rarely protective. The majority of strains was resistant to human serum and had a low level of adherence to Caco-2 cells. When tested for virulence in Galleria mellonella larvae, GNB strains had LD 50 values similar to that of safe controls. However, four strains, Hafnia paralvei 920, Proteus sp. (close to P. hauseri ) UCMA 3780, Providencia heimbachae GR4, and Morganella morganii 3A2A were highly toxic to the larvae, which suggests the presence of potential virulent factors in these strains. Noteworthy, to our knowledge, no foodborne intoxication or outbreak has been reported so far for any of the GNB belonging to the genera/species associated with the tested strains. The role of multiple dynamic interactions between cheese microbiota and GIT barriers could be key factors explaining safe consumption of the corresponding cheeses. Highlights: Gram negative bacteria (GNB) from cheeses are susceptible to pH 2 contrary to pH4. They have a low level of adherence to Caco-2 cells. LD50 in Galleria mellonella larvae mainly reveals values similar to safe controls. No foodborne intoxication or outbreak is reported so far for any of the GNB. Cheese microbiota and GIT barriers are key factors explaining safe status of GNB.